2011
DOI: 10.3844/ajebasp.2011.165.170
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Service Knowledge Management System in Integration of ITIL V3 and Enterprise Architecture

Abstract: Problem statement:This study attempts to investigate and clarify the relationship of Service Knowledge Management System (SKMS) with our primary study regard to using enterprise architecture through ITIL V3. Approach: SKMS concepts are introduced by ITIL V3 as a set of tools and databases that are used to manage knowledge and information of IT services. Results: The SKMS stores, retrieves, updates and presents all information that is expected for management of whole lifecycle of IT Services. Primary goal of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Moreover, the study suggest that knowledge transfer and support service does not influence perceived ease of use of EA. This result does not support findings from prior studies (McNabb and Barnowe, 2009;Nabiollahi et al, 2011) where the authors suggested that knowledge management positively determines EA use for IT management and public sector development. Likewise, Moscoso-Zea et al ( 2016) stated that availability of knowledge as support plays a substantial role towards user adoption of EA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study suggest that knowledge transfer and support service does not influence perceived ease of use of EA. This result does not support findings from prior studies (McNabb and Barnowe, 2009;Nabiollahi et al, 2011) where the authors suggested that knowledge management positively determines EA use for IT management and public sector development. Likewise, Moscoso-Zea et al ( 2016) stated that availability of knowledge as support plays a substantial role towards user adoption of EA.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings from the literature (McNabb and Barnowe, 2009) suggested that knowledge transfer is an important factor that influences practitioners' perceived usefulness and perceived ease of use of EAF. This is because the available of knowledge as information may help in enhancing practitioners' perceived ease of use and acceptance of EAF (Nabiollahi et al, 2011). Moreover, this factor encompasses how knowledge on the use of EA can be transferred to all practitioners involved within smart city development.…”
Section: Knowledge Transfermentioning
confidence: 99%
“…Hoshin Kanri business methodology emphasizes that the total involvement of all levels of employees should incorporate into their daily routines in order to achieve the organization's objectives (Parmenter, 2010). The goal of knowledge management process to enable organizations to improve the quality of management decision making by ensuring that reliable and secure information and data is available throughout the service lifecycle where the organization needs to focus Science Publications AJEAS on retrieving, sharing and utilizing their knowledge through problem solving, dynamic learning, strategic planning and decision making (Nabiollahi et al, 2011). People Development System (PDS) is a system that aims to:…”
Section: People Development System (Pds)mentioning
confidence: 99%
“…Thus, Knowledge is increasingly becoming the main asset (Kumar and Chhokar, 2011) that contributes to the competitive advantage of many organizations (Christine, 2011). As a consequence, Knowledge Management (KM) processes implementation is wide spread across different sectors in the contemporary knowledge era, starting from IT sector (Nabiollahi et al, 2011) to agricultural sector (Malekmohammadi, 2009). The KM also has been discussed from religious perspective (Yaakub, 2011) and at primary school level (Chongdarakul et al, 2010).…”
Section: Introductionmentioning
confidence: 99%